First person - Prasad, Vibhu (Journal of cell science, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Journal of Cell Science, helping early-career researchers promote themselves alongside their papers. Vibhu Prasad is co-first author on ‘Cell-to-cell and genome-to-genome variability of adenovirus transcription tuned by the cell cycle’, published in JCS. Vibhu conducted the research described in this article while a Research Associate/bridging postdoc in Professor Urs Greber's lab at Department of Molecular Life Sciences, University of Zurich, Switzerland. He is now a postdoc in the lab of Professor Ralf Bartenschlager at the Department of Infectious Diseases, Molecular Virology, University of Heidelberg, Germany, working on identification of cellular factors and processes required for flavivirus and SARS-CoV-2 infection.